EFFECTIVENESS OF THE KETOGENIC DIET IN TREATING SYMPTOMS OF AUTISM SPECTRUM DISORDER – A SYSTEMATIC REVIEW - Marta Danuta Cendrowska; Łukasz Brzost; Beata Choromańska; Julia Maszewska; Szymon Milnerowicz; Julia Procyk; Barbara Ponitka; Karolina Stępień; Justyna Berent; Paulina Rzepa; Aleksandra Klukowska; Wiktoria Szumlińska (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Autism spectrum disorder is a multifactorial condition characterised by challenges in interpersonal engagement, communication deficits and distinct behavioural patterns that deviate from typical developmental norms. While this condition is estimated to affect about 1 in 100 children worldwide, its treatment options are still limited. The purpose of this systematic review is to determine the potential of ketogenic diet - high-fat, low-carbohydrate regimen valued primarily for anticonvulsant qualities - in alleviating autism spectrum disorder clinical signs. Materials and methods: An extensive review of the literature was performed focusing on publications published since 2017. Results: Evidence suggests that the ketogenic diet influences metabolic activity of cells, display anti-inflammatory benefits, alter gut microbiota composition, positively influence mitochondrial activity and modulate brain function and behavioural phenotypes via epigenetic pathways. Therefore, ketogenic diet has emerged as a potentially effective therapeutic option in ameliorating ASD symptoms. Additionally, combining ketogenic diet with other therapeutic diets and their beneficial effects seems reasonable and justifiable. Conclusions: While these initial findings appear encouraging, extended research on larger and more diverse populations is required. Current evidence on the efficacy of ketogenic diet in treating symptoms of autism spectrum disorder is limited by variable study designs, small sample sizes, and frequently suboptimal adherence.